PENGEMBANGAN SOFT KILL PEMERINTAH DESA MOJOMALANG MOJOMALANG: STUDI PADA KASUS FITUR LAYANAN MANDIRI - Theresia Arcell Arinjani Marsudi (Sekolah Tinggi Pariwisata Mataram, 2022)
Digitization has been applied to all aspects of public life, one of which is public administration services. Effective and efficient services are the demands of society in today's era. However, it is different from the city for the problem of the quality of Human Resources. The village government and village communities must have qualified self-quality in the field of science and technology. Because to produce good service must be supported by self-quality development. The implementation of Village Digital Services is a program that is currently being pushed by the central government to advance village governments in developing governance and services provided to the community, this also encourages Mojomalang Village in Tuban Regency to be able to carry out village digitization. The program implemented by the Mojomalang Village Government is an administrative service system (Self Service). In realizing this goal, the current village government is required to be creative and innovative in the management of village governance. One of the innovations that can be made by the village government, especially Mojomalang Village, Parengan District, Tuban Regency in the field of public services is the Self Service Feature, either through the Mojomalang Village Receipt Website or the Android Application.